2021
DOI: 10.1080/15140326.2021.1922188
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric price adjustment and the effects of structural reforms and low demand in the gasoline market: the case of Greece

Abstract: The pricing mechanism in the gasoline market has often been the subject of public debate in Greece during the crisis years. Inefficient pricing could imply oligopolistic practices and losses to consumers' welfare. A way to test for inefficient pricing, is by testing for asymmetries in the adjustment of domestic gasoline prices to world oil price changes. The present paper tests for asymmetric adjustment of gasoline prices to oil price variations in the Greek market and examines whether the structural reforms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In contrast, others have identified no such causality patterns across the two markets under consideration (Kilian 2010 ). Finally, during crises, the literature also offers solid support for our findings (Asane-Otoo and Schneider 2015 ; Bragoudakis and Sideris 2021 ; Ogbuabor et al 2019 ). This literature evidence provides solid support for our empirical findings commensurate with the goal and the novelty of this work.…”
Section: Resultssupporting
confidence: 83%
“…In contrast, others have identified no such causality patterns across the two markets under consideration (Kilian 2010 ). Finally, during crises, the literature also offers solid support for our findings (Asane-Otoo and Schneider 2015 ; Bragoudakis and Sideris 2021 ; Ogbuabor et al 2019 ). This literature evidence provides solid support for our empirical findings commensurate with the goal and the novelty of this work.…”
Section: Resultssupporting
confidence: 83%
“…The authors did not find strong enough evidence of short- and long-term asymmetric effects of crude oil price shocks towards retail price for any of the four countries analyzed: contemporaneous and late effects are statistically similar in both. For the Greek economy, Bragoudakis and Sideris (2021) found only symmetrical effects with the TAR-ECM model.…”
Section: Resultsmentioning
confidence: 88%
“…Bragoudakis and Sideris (2021), in a study on asymmetry in Greece, using the TAR-ECM method, in the post-2010 period, observed evidence of a symmetrical behavior in the recent period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, his findings indicate that oligopolistic coordination is a more appropriate explanation of the observed asymmetry than theories related to the cost of search to consumers. In addition, studies of asymmetry in the gasoline market have been conducted in Italy [12], Greece [13], China [14], United States [15], Brazil [16], Russia [17], Australia [18], South Korea [19][20][21], Europe [22], and many countries [23]. The asymmetry study was applied not only to the gasoline market, but also to the electricity market [24] and the aviation market [25].…”
Section: Introductionmentioning
confidence: 99%